2006
DOI: 10.1186/1741-7015-4-18
|View full text |Cite
|
Sign up to set email alerts
|

Use of email in a family practice setting: opportunities and challenges in patient- and physician-initiated communication

Abstract: Background: Electronic mail (email) has the potential to improve communication between physicians and patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
55
0
10

Year Published

2009
2009
2015
2015

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(66 citation statements)
references
References 21 publications
1
55
0
10
Order By: Relevance
“…(Gaster et al, 2003) Controlled trials have shown that physicians respond to an average of 12-13 emails per week spending 5-10 minutes a day. (Virji et al, 2006) When email users in the general population were asked about their willingness to pay for email communication with their providers, 47% reported that they will not be willing to pay for email communications and 38% were ready to play 5-10 dollars. (Sittig et al, 2001) On the other hand, 42% of patients surveyed in the waiting room of a primary care clinic were willing to pay a small annual fee for this service.…”
Section: Attitudes and Barriers To Email Utilization By Physicians Anmentioning
confidence: 99%
See 2 more Smart Citations
“…(Gaster et al, 2003) Controlled trials have shown that physicians respond to an average of 12-13 emails per week spending 5-10 minutes a day. (Virji et al, 2006) When email users in the general population were asked about their willingness to pay for email communication with their providers, 47% reported that they will not be willing to pay for email communications and 38% were ready to play 5-10 dollars. (Sittig et al, 2001) On the other hand, 42% of patients surveyed in the waiting room of a primary care clinic were willing to pay a small annual fee for this service.…”
Section: Attitudes and Barriers To Email Utilization By Physicians Anmentioning
confidence: 99%
“…(Sittig et al, 2001) On the other hand, 42% of patients surveyed in the waiting room of a primary care clinic were willing to pay a small annual fee for this service. (Virji et al, 2006) Physicians had their concerns about the content of email communications. Physicians do not consider emails suitable for investigation of new symptoms or discussion of mental issues.…”
Section: Attitudes and Barriers To Email Utilization By Physicians Anmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the American College of Physicians (ACP) states that Be-communication between patients and physicians […] requires discussion and previous agreement before electronic exchange is initiated.^5 Although an estimated 20 % of physicians communicate with their patients by email, anecdotal evidence suggests that many do not engage their patients in discussion about e-communication prior to its occurrence. 6 Patients also appear more interested than their physicians in using online communication for clinical purposes, [7][8][9] perhaps because they face fewer barriers to entry than physicians, who must juggle concerns of institutional guidelines, liability, and the intrusion on their time. [7][8][9] According to the Pew Research Center, close to 90 % of U.S. adults use the Internet, and among these, 72 % visit social media websites like Facebook.…”
Section: Introductionmentioning
confidence: 99%
“…6 Patients also appear more interested than their physicians in using online communication for clinical purposes, [7][8][9] perhaps because they face fewer barriers to entry than physicians, who must juggle concerns of institutional guidelines, liability, and the intrusion on their time. [7][8][9] According to the Pew Research Center, close to 90 % of U.S. adults use the Internet, and among these, 72 % visit social media websites like Facebook. 10,11 Beyond socializing, users also turn to social media for health information; 12 % of Internet users have reported accessing social media to research health issues.…”
Section: Introductionmentioning
confidence: 99%